2011
DOI: 10.1002/hipo.20983
|View full text |Cite
|
Sign up to set email alerts
|

Periodically reactivated context memory retains its precision and dependence on the hippocampus

Abstract: Hippocampus is hypothesized to play a temporary role in the retrieval of context memories. Similarly, previous studies have reported that the expression of context memories becomes more generalized as memory ages. We report, first, that contextual fear memory expression changes from being sensitive to dorsal hippocampus inactivation by muscimol at 2 days post-conditioning, to insensitive at 28 days, and second, that over the same period rats lose their ability to discriminate between a novel and conditioned co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
50
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 21 publications
8
50
2
Order By: Relevance
“…Our observation of increased involvement of the ACC in remote memory is in line with previous research showing that, over time (after 2 weeks in rodents), the ACC becomes more involved in supporting contextual fear memory (Frankland et al, 2004;Goshen et al, 2011), whereas at the same time the involvement of the hippocampus is reduced (Anagnostaras et al, 1999;de Oliveira Alvares et al, 2012;Goshen et al, 2011;Kitamura et al, 2009;Ward et al, 1999;Wiltgen et al, 2010;Winocur et al, 2009). Our findings are also consistent with the idea that the hippocampus is critical for integrating information in a distributed cortical network representing various features of a memory, but as the memory trace matures, the ACC gradually takes over this integrative role and becomes critical for the expression of remote memory (Frankland and Bontempi, 2005).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our observation of increased involvement of the ACC in remote memory is in line with previous research showing that, over time (after 2 weeks in rodents), the ACC becomes more involved in supporting contextual fear memory (Frankland et al, 2004;Goshen et al, 2011), whereas at the same time the involvement of the hippocampus is reduced (Anagnostaras et al, 1999;de Oliveira Alvares et al, 2012;Goshen et al, 2011;Kitamura et al, 2009;Ward et al, 1999;Wiltgen et al, 2010;Winocur et al, 2009). Our findings are also consistent with the idea that the hippocampus is critical for integrating information in a distributed cortical network representing various features of a memory, but as the memory trace matures, the ACC gradually takes over this integrative role and becomes critical for the expression of remote memory (Frankland and Bontempi, 2005).…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with the transformation hypothesis according to which the hippocampus supports detailed, context-specific memories, which are over time transformed into gist-like, context-unspecific representations supported The anterior cingulate and generalized memory E Ö Einarsson et al by cortical structures (Winocur et al, 2010). This posited role of the hippocampus in supporting context memory precision is supported by recent studies showing (a) that inactivation of the dorsal hippocampus disrupts the expression of context-specific fear memory, but not the expression of generalized fear memory (de Oliveira Alvares et al, 2012;Wiltgen et al, 2010) and (b) that inhibitory connectivity in the mossy fibers of the dorsal hippocampus are critical for maintaining context-specificity of contextual fear memory (Ruediger et al, 2011). Previous studies have demonstrated that brief re-exposure to a training context at remote time points can reinstate context-specific memory expression, an effect that lasts from 1 h (Zhou and Riccio, 1994), up to at least 24 h (Wiltgen and Silva, 2007).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Studies using animal models have described how memories that are initially dependent upon the hippocampus for retrieval become independent of that structure over time, a process hypothesized to reflect neocortical traces becoming sufficiently strong to support retrieval (McClelland et al 1995). A number of studies have found such a gradient for contextual fear conditioning for the hippocampus, where inactivating the structure impairs recent but not remote memory (.14 d old), suggesting decreased involvement of the structure in memory retrieval over weeks following memory acquisition (Kim and Fanselow 1992;Anagnostaras et al 1999;Ward et al 1999;Kitamura et al 2009;Wiltgen et al 2010;de Oliveira Alvares et al 2012; but see Goshen et al 2011). Conversely, the opposite gradient has been found for the involvement of the ACC where pharmacological inactivation impairs remote memory expression but not recent memory, suggesting increased involvement as the memory ages ).…”
mentioning
confidence: 99%
“…In this sense, the hippocampus and the amygdala appear to be specifically involved in the contextual effects on conditioning, depending on the type of learning paradigm. The hippocampus seems to be involved in memory processes and contextual learning [136], mainly in the paradigm of fear conditioning and in spatial tasks, such as the Morris water-maze [137][138][139]. Some reports also suggest that the amygdala is part of the brain mechanism that allows the context to influence fear conditioning [140][141][142] and place conditioning [143].…”
Section: Effects Of Context On Taste Learningmentioning
confidence: 99%